Los Parlamentos Mapuche, una perspectiva desde las fuentes del derecho internacional - Zubeldía Cascón, Florencia (2021)
This paper will analyze the Mapuche Parliaments, signed between the Mapuche people and Spain in the 17th century, particularly the Quillín Parliament (1641), from the perspective of the sources of international law. To do this, the specificities of these instruments will be studied with consideration of the law of treaties while accounting for historical context and the specific situations of all involved individuals. These matters will be analyzed through a modern lens while taking into account Latin America's colonization